2018
DOI: 10.1182/bloodadvances.2017011510
|View full text |Cite
|
Sign up to set email alerts
|

Mutational dynamics of early and late relapsed childhood ALL: rapid clonal expansion and long-term dormancy

Abstract: Key Points• Two distinct evolutionary patterns govern early and late relapse.• Evolutionary patterns suggest a mutationdriven resistance for early relapses and a reexpansion of dormant cells for late ones.Childhood acute lymphoblastic leukemia (cALL) is the most frequent pediatric cancer.Refractory/relapsed cALL presents a survival rate of ;45% and is still one of the leading causes of death by disease among children. Mechanisms, such as clonal competition and evolutionary adaptation, govern treatment resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 46 publications
2
31
0
Order By: Relevance
“…In ETV6-RUNX1 ALL, there is a striking over-representation of RAG-mediated genomic mutational process 59 , plausibly linked to inflammation/infection-related activation of these recombination events 60 . In contrast, leukemia evolution plays a completely different role during ALL therapy, often times as a primary means of evasion of cytotoxic effects of chemotherapy 61 . Somatic mutations in key drug targets of metabolizing genes (e.g., NT5C2 and PRPS1) have been identified specifically at the time of ALL relapse and are shown to confer dramatic resistance to anti-leukemic agents 62,63,64 .…”
Section: Recent Advances From International Collaborative Studiesmentioning
confidence: 99%
“…In ETV6-RUNX1 ALL, there is a striking over-representation of RAG-mediated genomic mutational process 59 , plausibly linked to inflammation/infection-related activation of these recombination events 60 . In contrast, leukemia evolution plays a completely different role during ALL therapy, often times as a primary means of evasion of cytotoxic effects of chemotherapy 61 . Somatic mutations in key drug targets of metabolizing genes (e.g., NT5C2 and PRPS1) have been identified specifically at the time of ALL relapse and are shown to confer dramatic resistance to anti-leukemic agents 62,63,64 .…”
Section: Recent Advances From International Collaborative Studiesmentioning
confidence: 99%
“…Previous studies have used allele frequency (AF) thresholds to define mutations as being present in a minor subclonal or major clone (clonal) ranging between 20% and 30% [5][6][7][8] . In this study, we used an AF threshold of 25% to separate major clonal from subclonal alterations, since mutations below 25%…”
Section: Defining Clonal and Subclonal Alterationsmentioning
confidence: 99%
“…Another study found the presence of at least two distinct genetic subclones in five out of six patients using targeted single-cell DNA sequencing 9 . In this context, we reported different clonal dynamics between early (during treatment) and late (>36 months after diagnostic) bone marrow relapse events and showed variable clonal origin in late relapse events 10 .…”
Section: Introductionmentioning
confidence: 83%